Intensity vs. volume in professional soccer: Comparing congested and non-congested periods in competitive and training contexts using worst-case scenarios - Douchet, T.; Michel, A.; Verdier, J.; Babault, N.; Gosset, M.; Delaval, B. (Sports, 2025)
Background: Understanding the balance between intensity and volume during training and competition is crucial for optimizing players` performance and recovery in professional soccer. While worst-case scenarios (WCSs) are commonly used to assess peak match demands, little is known about how the time spent within WCS thresholds varies across congested and non-congested periods, especially when considering differences in playing time. This study examines the time spent at different percentages of WCSs during congested and non-congested periods for players with lower and higher playing times throughout training sessions and matches.